2018
DOI: 10.2147/ijn.s163206
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and evaluation of graphene oxide scaffold for periodontal wound healing of class II furcation defects in dog

Abstract: IntroductionThe 3-dimensional scaffold plays a key role in volume and quality of repair tissue in periodontal tissue engineering therapy. We fabricated a novel 3D collagen scaffold containing carbon-based 2-dimensional layered material, named graphene oxide (GO). The aim of this study was to characterize and assess GO scaffold for periodontal tissue healing of class II furcation defects in dog.Materials and methodsGO scaffolds were prepared by coating the surface of a 3D collagen sponge scaffold with GO disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 43 publications
(42 reference statements)
1
51
0
Order By: Relevance
“…Therefore, researchers are working on fabricating novel micronano scaffolds to drive angiogenesis and promote bone regeneration [20]. The common method is infiltration of nanoparticles, nanosheets or nanofibres in different natural or synthetic materials, such as bioceramics [21,22], polycaprolactone [23], chitosan [24], silk fibroin [25] and collagen [26][27][28]. The composition of nanomaterials improves the mechanical properties and surface hydrophilicity of the bone tissue engineering scaffold, which is beneficial to the growth and adhesion of human umbilical vein endothelial cells (HUVECs) [29].…”
Section: Bone Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, researchers are working on fabricating novel micronano scaffolds to drive angiogenesis and promote bone regeneration [20]. The common method is infiltration of nanoparticles, nanosheets or nanofibres in different natural or synthetic materials, such as bioceramics [21,22], polycaprolactone [23], chitosan [24], silk fibroin [25] and collagen [26][27][28]. The composition of nanomaterials improves the mechanical properties and surface hydrophilicity of the bone tissue engineering scaffold, which is beneficial to the growth and adhesion of human umbilical vein endothelial cells (HUVECs) [29].…”
Section: Bone Tissue Engineeringmentioning
confidence: 99%
“…Bone engineering Nano-HA (1) In vitro study (2) In vivo glucocorticoid-induced bone defect model [28] In vitro study [29,33,154,155] In vivo ectopic osteogenesis study [18] In vivo calvarial defect model [20,99] Micro/Nano-structured surfaces of Cu x -HA (1) In vitro study (2) In vivo subcutaneously implant study [34] TCP nanolayers In vitro study [21] Nanofibrin In vitro study [24] GO In vivo calvarial defect study [22,26] In vivo ectopic osteogenesis study [27] PCL nanofibrous biomembranes In vivo maxillary bone lesion model [16] Mesoporous bioactive glass nanoparticles (1) In vitro study (2) In vivo ectopic osteogenesis study [30] Copper doped in electrospun bioactive glass nanofibers…”
Section: Nanomaterials Type Of Angiogenesis Assays Referencesmentioning
confidence: 99%
“…In addition to its mechanical and electrical properties, graphene functionalization with protein/peptides will be useful for tissue engineering applications [ 63 ]. For example, Kawamoto and coworkers [ 64 ] prepared graphene oxide scaffolds (GO). They demonstrated that they presented a quite low cytotoxicity and that they were able to enhance the cellular ingrowth behavior.…”
Section: Graphenementioning
confidence: 99%
“…The excellent electrical conductivity and charge carrier mobility of graphene has enabled this material to be beneficial for the development of electronic devices [ 22 ], and now it is widely used in several biomedical applications, including biosensors, drug and gene delivery, cell imaging devices, electrical stimulation of cells, phototherapy for cancer, bioassays [ 23 , 24 , 25 , 26 , 27 ], and as the substrate for anchorage-dependent cells [ 24 , 28 , 29 , 30 , 31 ]. Graphene oxide (GO), a graphene nanosheet with oxygen-containing groups [ 32 ], has been reported to improve the properties of bioscaffolds for tissue transplantation, in particular for bone tissue [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. In addition, GO-enriched bioscaffolds have several advantages, including low cytotoxicity [ 37 ] and higher physical strength [ 38 ], and exhibit promising biocompatibility [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene oxide (GO), a graphene nanosheet with oxygen-containing groups [ 32 ], has been reported to improve the properties of bioscaffolds for tissue transplantation, in particular for bone tissue [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. In addition, GO-enriched bioscaffolds have several advantages, including low cytotoxicity [ 37 ] and higher physical strength [ 38 ], and exhibit promising biocompatibility [ 36 ]. Substrates coated with GO have also been demonstrated to provide excellent interfaces for cell–scaffold interaction in vitro [ 31 ].…”
Section: Introductionmentioning
confidence: 99%